EXPERIENCE OF REMOTE OBSTETRIC CENTERS IN THE KEMEROVO REGION IN THE CONTEXT OF A NEW CORONAVIRUS INFECTION - Светлана Ивановна Елгина; Ирина Анатольевна Ушакова; Елена Владимировна Рудаева; Нонна Марковна Шибельгут; Вадим Гельевич Мозес (Медицина в Кузбассе, 2020)
Aim – to determine the effectiveness of dynamic monitoring and routing of pregnant women, women in labor and maternity hospitals in the context of the spread of a new coronavirus infection in obstetric remote consultation centers.